Pelatihan Musik Berbasis Komunitas di House of Joy Desa Oemat Nunu, Kupang Barat, Kabupaten Kupang - Iswanto; Bara Pa, Hemi D.; Kabnani, Jefri S.; Salau, Triati L.; Nulik, Cici; Bauana, Agnes E.; Saefatu, Apris Y.; Tafuakan, Philby; Koli, Maria; Thoomaszen, Friandy W. (Institut Agama Kristen Negeri Kupang, 2022)
Community Music Learning (CML) is music learning approach that is not tied to a music grade but rather to the musical skills possessed by the community. This is important given the number of music communities in the province of East Nusa Tenggara (NTT) which is so many and diverse. These communities include, (1) the church; (2) schools; (3) studio; and (4) the music community in the community. This fact is constantly being studied so that this year the Church Music Education Study Program (PMG), the State Christian Religious Institute (IAKN) Kupang conducted PKM in one of the communities that is considered representative of this theory and phenomenon. Total activities carried out as many as 25 activities for 2 months. This activity focuses on the development of musical competence in a wide range of aspects. Aspects related to music in this community are (1) dance; (2) theater; (3) psychology and counseling. The training activities have been carried out well. The PKM that has been implemented provides some input, including broad aspects of music can continue to be developed with various approaches. Another important thing is that continuous efforts are needed to be able to reach more communities in the province of East Nusa Tenggara (NTT).